Prognostic implication of left ventricular hypertrophy regression after antihypertensive therapy in patients with hypertension - Kim, Hyue Mee; Hwang, In-Chang; Choi, Hong-Mi; Yoon, Yeonyee Elizabeth; Cho, Goo-Yeong (Frontiers in Cardiovascular Medicine, 2022)
Background: Left ventricular (LV) hypertrophy (LVH) in patients with hypertension is a significant risk factor for cardiovascular mortality and morbidity. However, the prognostic implication of LVH regression after antihypertensive therapy has not been clearly investigated. Methods: Patients who underwent echocardiography at the time of the diagnosis of hypertension and repeated echocardiography at an interval of 6-18 months were retrospectively identified. LVH was defined as LV mass index (LVMI) >115 g/m2 (men) and >95 g/m2 (women). LVH regression was defined as LVH at initial echocardiography with normal geometry or concentric LV remodeling at follow-up echocardiography. Cardiovascular mortality, hospitalization for heart failure (HHF), coronary revascularization, stroke, and aortic events were analyzed according to changes in LVMI and geometry. Results: Of 1,872 patients, 44.7% (n=837) had LVH at the time of diagnosis; among these, 30.7% showed LVH regression. The reduction in LVMI was associated with the reduction in BP, especially in those with LVH at baseline. During follow up (median, 50.4 months; interquartile range, 24.9–103.2 months), 68 patients died of cardiovascular causes, 127 had HHF, and 162 had vascular events (coronary revascularization, stroke, and aortic events). Persistent or newly-developed LVH during antihypertensive therapy was a significant predictor of cardiovascular mortality and events, especially HHF. On multivariable analysis, women, diabetes, atrial fibrillation, coronary artery disease, larger LVMI and end-diastolic dimension, and less reduction in systolic BP were associated with persistent or newly-developed LVH. Conclusion: LVH regression in patients with hypertension is associated with a reduction in cardiovascular events and can be used as a prognostic marker.